Quantifying the impact of inhalational burns: a prospective study - Si Jack Chong; Yee Onn Kok; Rosanna Xiang Ying Tay; Desai Suneel Ramesh; Kok Chai Tan; Bien Keem Tan (Burns & Trauma, 2018)
Abstract Background Inhalational injury is a major cause of morbidity and mortality in burns patients. This study aims to analyse the clinical outcomes, complications and bacteriology of inhalational burn patients. Methods A prospective study was done on consecutive admissions to Burn Department, Singapore General Hospital over 15 months from January 2015 to March 2016. Presence of inhalational injury, demographics, complications and outcomes was recorded. Diagnosis of inhalational injury was based on history, symptoms and nasoendoscopy. Diagnosis of acute respiratory distress syndrome (ARDS), acute kidney injury (AKI) and infective complications were according to the Berlin criteria, acute kidney injury network (AKIN) classification stage 2 and above and the American Burns Association guidelines. Results Thirty-five patients (17.3%) had inhalational burns out of 202 patients (63.4% male, 57.4% Chinese population). The average age was 43 ± 16.7 years (range 16–86), and percentage of total body surface area (%TBSA) was 12.1 ± 18.0 (range 0–88). In patients with inhalational injury, age was 38.9 ± 17.2 years and %TBSA was 30.3 ± 32.3. In patients without inhalational injury, age was 44.1 ± 12.8  years and %TBSA was 8.3 ± 9.59. Compared to patients with cutaneous injury alone, patients with inhalational burns had more surgeries (3 ± 7.07 vs 1 ± 1.54, p = 0.003), increased length of stay (21 days vs 8 days, p = 0.004) and higher in-hospital mortality rate (17.1% vs 0.6%, p < 0.001). Incidence of ARDS and AKI was 48.6% and 37.1%, respectively, compared to 0.6% and 1.2% in the patients without inhalational injury (p < 0.001). Patients with inhalational injury had increased incidence of bacteraemia (31.4% vs 2.4%, p < 0.001), pneumonia (37.1% vs 1.2%, p < 0.001) and burn wound infection (51.4% vs 25.1%, p = 0.004). Inhalational injury predicted AKI with an adjusted odds ratio (OR) of 17.43 (95% confidence interval (CI) 3.07–98.87, p < 0.001); ARDS, OR = 106.71 (95% CI 12.73–894.53, p < 0.001) and pneumonia, OR = 13.87 (95% CI 2.32–82.94, p = 0.004). Acinetobacter baumannii was the most frequently cultured bacteria in sputum, blood and tissue cultures with inhalational injury. Gram-negative bacteria were predominantly cultured from tissue in patients with inhalational injury, whereas gram-positive bacteria were predominantly cultured from tissue in patients without inhalational injury. Conclusions Inhalational injury accompanying burns significantly increases the length of stay, mortality and complications including AKI, ARDS, infection and sepsis.